The heat kernel in Riemann normal coordinates and multiloop Feynman graphs in curved spacetime - Igor Carneiro; Gero von Gersdorff (Journal of High Energy Physics)
Abstract We present a formalism for computing arbitrary scalar multi-loop Feynman graphs in curved spacetime using the heat kernel approach. To this end, we compute the off-diagonal components of the heat kernel in Riemann normal coordinates up to second order in the curvature.